BioHerbWebs: a mobile knowledge portal for bioinformatics community of practice with a collaborative environment - Abdullah, Rusli; Selamat, Mohd Hasan; Jaafar, Azmi; Napis, Suhaimi; Wan Maya Othman, Wan Noor Rafida; Wan Ishak, Wan Roslina (International Journal of Computer Science and Network Security, 2008)
BioHerbWebs is a mobile Knowledge Management System (mKMS) or mobile knowledge portal is a system that supports, creates, captures, stores and disseminates expertise and knowledge in a collaborative environment. The idea of mKMS is to ensure that the right knowledge is delivered to the right person just in the right time using the mobile devices. However, locally, we have never heard about mKMS since it is stll a new area that are still evolving. In this paper, we propose the system development and implementation that might be useful to support community of practice (CoP) in bioinformatics domain which hoping that this research can be served as a guidance for future reference in developing mKMS in any other related field.